2022
DOI: 10.1080/21505594.2022.2064596
|View full text |Cite
|
Sign up to set email alerts
|

PHB2 affects the virulence of Vip3Aa to Sf9 cells through internalization and mitochondrial stability

Abstract: The vegetative insecticidal proteins (Vip3A) secreted by some Bacillus thuringiensis (Bt) strains during vegetative growth are regarded as a new generation of insecticidal toxins. Like insecticidal crystal proteins, they are also used in transgenic crops to control pests. However, their insecticidal mechanisms are far less defined than those of insecticidal crystal protein. Prohibitin 2 (PHB2) is a potential Vip3Aa binding receptor identified from the membrane of Sf9 cells in our previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…In our previous study, we found the dual functions of PHB2 in the Vip3Aa action process: (i) PHB2 mediates the internalization of Vip3Aa by interacting with it and (ii) PHB2 is an essential structural protein for mitochondrial stability and helps cells resist Vip3Aa virulence. The latter was more important than the former for Vip3Aa toxicity, suggesting a critical role of PHB2 in mitochondria for cellular resistance 12 . PHB1 and PHB2 form ring‐like structures with high molecular weights in yeast, nematodes and mammals, and this complex performs multiple functions to maintain the structure and regulate the function of mitochondria 19 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, we found the dual functions of PHB2 in the Vip3Aa action process: (i) PHB2 mediates the internalization of Vip3Aa by interacting with it and (ii) PHB2 is an essential structural protein for mitochondrial stability and helps cells resist Vip3Aa virulence. The latter was more important than the former for Vip3Aa toxicity, suggesting a critical role of PHB2 in mitochondria for cellular resistance 12 . PHB1 and PHB2 form ring‐like structures with high molecular weights in yeast, nematodes and mammals, and this complex performs multiple functions to maintain the structure and regulate the function of mitochondria 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In our previous research, 48 h was a suitable time point to detect the virulence of Vip3Aa to Sf9 cells. 12 Based on this, we tested the virulence of Vip3Aa to Sf9 cells, and the LC 50 of Vip3Aa to Sf9 cells at 48 h was 82.1 ± 10.6 μg mL −1 . Then, we chose a sublethal concentration (60 μg mL −1 ) for the following experiments.…”
Section: (A) (B))mentioning
confidence: 99%
See 2 more Smart Citations
“…Binding to the receptor is a crucial step in the virulence process of Vip3A. Recently, several Vip3A receptors have been identified, including ribosome S2 protein from sf21 cells of S. frugiperda [ 12 ], scavenger receptor class C protein (Sf-SR-C) [ 13 ], fibroblast growth factor receptor protein (Sf-FGFR) [ 14 ] and prohibitin 2 (PHB2) from the Sf9 cell lines of S.frugiperda [ 15 ], and a tenascin-like glycoprotein from A. ipsilon [ 16 ]. After binding to its receptor, Vip3A may exert its potency through pore formation and induce apoptosis [ 1 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%